Estudo de associação de polimorfismos nos genes MTHFR, PICALM, EPHA1, ECA e Cat-D na Doença de Alzheimer - Camporez, Daniela (2014)
Alzheimer Disease (AD) is progressive neurodegenerative pathology in brain that is clinically characterized by the loss of memory and cognition. The major risk factor to the development of the disease is advanced age, with a complex interaction of environment and genetic factors that together can increase the incidence of the disease. Several polymorphisms were studied to verify their relations with AD all over the world. The confirmation of a positive association of a determined polymorphism in different populations can contribute to the identification of specific genes that cause the disease. This study had as its aim to evaluate the potencial risk of the genetic variations to the Alzheimer Disease in the population of Vitória-ES. The polymorphisms rs3851179 of the MTHFR gene, rs3851179 of the PICALM gene, rs11767557 of the EPHA1 gene, rs387906576 ECA and rs74315304 Cat-D were analized throught the technique of PCR-RFLP in an case: control study. The polymorphisms of the genes MTHFR and PICALM demonstrated a positive association with the disease in question. To the polymorphism of the MTHFR gene, the genotype CT showed statistically significative values (p= 0.030) sugesting that the T allele behaves itself as a factor of risk to the disease in the population of Vitória-ES. However, with a small effect on the etiology of the disease. The MTHFR gene has a central role in the metabolism of the folate (acid folic) and homocystein, important components to the functioning of the central nervous system in all ages. Polymorphism variations in this gene can diminish the enzymatic activity increasing the chance in the AD development. The polymorphism GG of the PICALM gene showed to be statistically associated with AD (p= 0.033), the PICALM protein is expressed in all tissues with a major detectable expression in the neurons where it is distributed in the structures of synaptic cracks. But the polymorphisms of the Cat-D , ECA and EPHA1 genes did not show significative statistic association to the AD in the population of Vitória-ES. These results improve our knowledge about the alleles of risk to AD, enabling the criation of a genetic profile of susceptibility to the studied population.